The Influence of Organizational Culture, HR Competence, Digital Technology, and Marketing Strategy on MSME Development in the Era of Digital Transformation - Handayani, Eka; Wahyu, Wahyu; Sari, Yusnita; Feronicha, Marissa; Hidayati, Tetra (OMNICODE Journal (Omnicompetence Community Developement Journal), 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia play a strategic role in supporting the national economy but still face significant challenges in the digital transformation era. This study aims to analyze the synergy between organizational culture, human resource (HR) competencies, digital technology, and marketing strategies in MSME development. Based on a literature review, the findings indicate that these four factors are interconnected and mutually reinforcing. An innovative organizational culture drives the enhancement of human resource competencies, while digital technology provides tools to support the implementation of effective marketing strategies. This synergy can be achieved through a holistic approach involving collaboration among the government, private sector, and educational institutions. With an integrated strategy, MSMEs can enhance their competitiveness and achieve sustainable growth.